مهارات المحاسبين الإداريين المطلوبة لمواكبة تطور مهنة المحاسبة الإدارية - ديك رولى (Latakia University Journal - Economic and Legal Sciences Series, 2018)
ازدادت التحديات المعاصرة على مهنة المحاسبة لتتطور في مجالات وانواع جديدة. الامر الذي ادى الى ازدياد الحاجة الى تطور مجال المحاسبة الإدارية (MA) فيما يتعلق بالتعريفات والوظائف والادوات الجديدة فيها من اجل تطوير وتحسين نتائج الأعمال والمراكز المالية في الشركات. يهدف هذا البحث الى استكشاف آفاق جديدة لهذا المجال في مهنة المحاسبة الإدارية. يقدم البحث مجموعة من المفاهيم المختلفة التي يمكن أن تساهم في فهم التحديات الأساسية في المحاسبة الإدارية وكما يوضح كيف يمكن تمييز المحاسبين عن غيرهم من المهنيين. يهدف هذا البحث ايضاً الى ابراز تعريفات أكثر تحديدًا لمهنة المحاسبين الإداريين وتحليلها ومناقشة دورها في رفع اداء العمل في الشركات مما يساهم أيضاً في زيادة ارباحها. توصلت الدراسة الى أن المحاسبين الإداريين لابد أن يمتلكوا مجالاً واسعاً من المهارات، حيث انه يمتلكون حالياً مستوى من المعرفة يغطي المجالات التقليدية مثل إدارة التكلفة، تحليل المالي، وتقييم الأصول. لذلك لابد من تطوير معرفتهم ومهاراتهم لتشمل المجالات الناشئة والجديدة مثل المسؤولية الاجتماعية، محاسبة التلوث البيئي وإدارة المخاطر، ليعمل كشريك استراتيجي مع فريق الادارة العليا في الشركات. Contemporary challenges to the accounting profession, have been grown to new areas and types. This has led to an increase in the need for developing new management accounting (MA), in terms of concept, functions and new tools, in order to develop and improve the financial profit of companies in the business. This research aims to explore new understanding and horizons for this field of accounting profession. The research presents a range of different concepts that can contribute to understanding the basic challenges in management accounting and also illustrates how accountants can be distinguished from other professionals. The purpose of this research is to highlight more specific definitions of the profession of management accountants, analyze them. And the paper discuss the role of management accountants in raising the performance in companies, which also contributes to business profit. The study found that management accountants must have a wide range of skills, as they currently have a level of knowledge covering only traditional areas such as cost management, financial analysis, and asset evaluation. This research concluded that, their knowledge and skills therefor, should be developed to include new areas such as social responsibility, environmental pollution accounting, and risk management, to enable them to be as a strategic partner with the management team.